Developing teaching materials for writing observation report texts using Powtoon for grade X high school students - Karina, Agidia; Sinaga, Mangatur; Charlina, Charlina (Univeritas Papua, 2024)
This study aims to develop teaching materials for writing observation report texts based on technology by utilizing the Powtoon application for class X SMA students. This study uses a development procedure called the ADDIE model. This study was conducted at SMA Negeri 15 Pekanbaru with 36 class XB students as research subjects. The data collection techniques used were student needs analysis questionnaires, validation questionnaires for teaching material products by validators, trials (limited tests), and teacher and student assessment questionnaires. The results showed that the quality of the product development of teaching materials for writing observation report texts based on Powtoon for class X SMA students was seen from the results of expert validation and got a score of 4.5 (90%), the practicality of the product was seen from the results of teacher assessments of 4.6 (92%) and student assessments of 4.5 (90%). The average pre-test score was 64, and the post-test was 87, which was stated to be significantly different based on the Wilcoxon test. It can be concluded that teaching materials designed using Powtoon for class X SMA students are very feasible and have the potential to be used in learning to write observation report texts.